(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
Everyone who has had the opportunity to experience the most valuable aspect of the educational process - that is, its influence on the shaping and flourishing of the human potential of the individual - seems to be able to capture, albeit intuitively, the deep, philosophical meaning of the term “teacher”. In this meaning, it refers not only to a professional, but also – or even primarily – to a spiritual category. A teacher is a person who, through words and deeds, reveals to us the true meaning of the lifelong activity of learning, understood as a process of self-development and self-actualization, as recognizing the unique ontological “gift of the self” and nurturing it towards achieving its optimal form. It is a process based on the acquisition of knowledge of various kinds, but always inspired by the ethical pursuit of the good and aimed at establishing a delicate balance between one’s own and other persons’ perspectives.